Biofuels and Economic Welfare: A cost-benefit analysis of Jatropha schemes in Zimbabwe - Banarbas Mawire (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2008)
The promotion of oil producing plants for production of biofuel has come to the fore most recently as a result of the concept of it being used to try and uplift livelihoods among rural communities. There are many arguments in favour and against biofuels. However, a current debate focuses on the possible negative social and environmental implications, especially with regards to land competition and sustainability assurance. There has been growing concern on taking arable land out of food production and allocating its use to production of energy crops. Experience gained with the establishment of Jatropha hedges, collection of Jatropha seeds, oil extraction and use of Jatropha oil to run diesel engines present a tremendous potential for developing rural industries and utilizing bio fuel energy. However, establishing oil milling plants as a strategy to provide energy to remote and scattered rural villages requires substantial investment amounts of money and therefore this justifies the need for doing an evaluation to objectively verify the financial viability and economic desirability of the schemes. Interestingly, this analysis of Jatropha hedges and oil milling schemes in rural Zimbabwe shows that energy crops such as Jatropha have the potential for increasing increasing the economic welfare of people in the rural areas.
Keywords: 330; Zimbabwe; Biofuel; Biokraftstoff; Bioenergie; Ölfrucht; Kosten-Nutzen-Analyse; Simbabwe